Fermentation kinetics and in vitro degradation rates of grasses of the genus Cynodon - Reis, Sidnei Tavares Dos; Lima, Marcus Vinícius Gonçalves; Sales, Eleuza Clarete Junqueira De; Monção, Flávio Pinto [UNESP]; Rigueira, João Paulo Sampaio; Santos, Leonardo David Tuffi (Editora da Universidade Estadual de Maringá - EDUEM, 2016)
The present study aimed to evaluate the fermentation kinetics and degradation rates of Cynodon grasses estimated by semi-automated technique of in vitro gas production. The forages were: Coastcross, Tifton 85 and Tifton 68. Pressure readings were taken at 0, 2, 4, 6, 8, 10, 12, 15, 19, 24, 30, 36, 48, 72 and 96 hours. Dry matter degradability (DMD) was obtained by the percentage of dry matter (DM) remaining after 0, 6, 12, 24, 48 and 96 hours of fermentation. Tifton 85 showed a higher total gas production (p <0.05). Higher fermentation rates were found at the beginning of fermentation followed by subsequent reduction (p <0.05) over time. Tifton 85 and Tifton 68 showed higher values (p < 0.05) for soluble fraction, potentially degradable insoluble fraction, insoluble fraction, potential and effective degradability of dry matter in relation to Coastcross grass. Higher gas production during in vitro incubation of dry matter was observed for Tifton 85 g.

Objetivou-se avaliar a cinética da fermentação e taxas de degradação de gramíneas do gênero Cynodon estimadas pela técnica semi automática de produção de gases in vitro. As forrageiras utilizadas foram: Coastcross, Tifton 85 e Tifton 68. As leituras de pressão foram realizadas nos tempos: 0, 2, 4, 6, 8, 10, 12, 15, 19, 24, 30, 36, 48, 72 e 96h. A degradabilidade da matéria seca (DMS) foi obtida pela porcentagem de matéria seca (MS) remanescente após 0, 6, 12, 24, 48 e 96h de fermentação. A gramínea Tifton 85 apresentou uma produção total de gases superior (p <0,05). Maiores taxas de fermentação ocorreram no tempo inicial de fermentação decrescendo (p <0,05) com o avançar do tempo. As gramíneas Tifton 85 e Tifton 68 apresentaram valores superiores (p <0,05) de fração solúvel, insolúvel potencialmente degradável, insolúvel, degradabilidade potencial e efetiva da matéria seca em relação à gramínea Coastcross. Maior produção de gases durante a incubação in vitro da matéria seca foi observada para o capim Tifton 85.
Cinética da fermentação e taxa de degradação in vitro de gramíneas do gênero Cynodon
Keywords: forage; gas production; semi-automated technique; forragem; produção de gás; técnica semi automática